2020
DOI: 10.14742/ajet.6388
|View full text |Cite
|
Sign up to set email alerts
|

Data in practice: A participatory approach to understanding pre-service teachers’ perspectives

Abstract: Data about learning can support teachers in their decision-making processes as they design tasks aimed at improving student educational outcomes. However, to achieve systemic impact, a deeper understanding of teachers’ perspectives on, and expectations for, data as evidence is required. It is critical to understand how teachers’ actions align with emerging learning analytics technologies, including the practices of pre-service teachers who are developing their perspectives on data use in classroom in their ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Collaborations between this institution and research institutions have focused on researching educational data ethics issues involved in learning analytics, particularly in higher education and in classroom contexts. For example, they explored how educational data ethics issues are addressed and resolved from the perspective of pre-service teachers (Prestigiacomo et al, 2020).…”
Section: Label (Llr)mentioning
confidence: 99%
“…Collaborations between this institution and research institutions have focused on researching educational data ethics issues involved in learning analytics, particularly in higher education and in classroom contexts. For example, they explored how educational data ethics issues are addressed and resolved from the perspective of pre-service teachers (Prestigiacomo et al, 2020).…”
Section: Label (Llr)mentioning
confidence: 99%
“…Prestigiacomo R. et al found that teachers have a preference for data-related technologies by examining workshops related to teachers' data technology competencies. They noted that creating more instructional practices and corresponding training in data technologies improves pre-service teachers' data literacy, which in turn better enhances teaching and learning [14]. Wu, M. S. et al conducted a study to analyze how information literacy affects job performance, and the results showed that information literacy positively affects job performance through the intermediate channel of creativity [15].…”
Section: Introductionmentioning
confidence: 99%
“…Fangbo Hou. Applied Mathematics and Nonlinear Sciences, 9(1) (2024)[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] …”
mentioning
confidence: 99%
“…With this approach, it is expected to identify general patterns in the use of specific pedagogical strategies and their correlation with student learning outcomes. A participatory approach will also be adopted to gain direct insights from students and faculty regarding their experiences in the learning process (Prestigiacomo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%